Reconciling household goals in southern African woodlands using weighted goal programming - Kowero, G.S.; Nhantumbo, I.; Tchale, H. (2005)
Weighted goal programming (WGP) is employed to reconcile the goals of food security, improved incomes and woodland conservation in households from selected sites in Malawi, Mozambique and Zimbabwe. The three goals are attainable simultaneously, albeit with trade-offs useful in guiding development of rural development policies. The WGP model provides a framework for evaluating impact, on the household goals and woodland condition, of some macroeconomic and sectoral policies and demographic changes. Keywords: goal programming, woodlands, households, simulation, southern Africa.